Japan : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This Selected Issues paper analyzes the key features of the Japanese business cycle, and investigates whether the current recovery differs from past recoveries. In particular, this paper poses the following questions: what are the main characteristics of Japanese business cycles since 1980, and what happens to output, expenditure components, and prices over the cycle? The paper reviews the recent performance and policy issues with respect to the banking sector, insurance sector, and public financial sector in Japan. The stability of the financial sector is also assessed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet